Effect of triploidy on liver gene expression in coho salmon (Oncorhynchus kisutch) under different metabolic states - Christensen, Kris A. (BMC Genomics, 2019)
BACKGROUND: Triploid coho salmon are excellent models for studying gene dosage and the effects of increased cell volume on gene expression. Triploids have an additional haploid genome in each cell and have fewer but larger cells than diploid coho salmon to accommodate the increased genome size. Studying gene expression in triploid coho salmon provides insight into how gene expression may have been affected after the salmonid-specific genome duplication which occurred some 90 MYA. Triploid coho salmon are sterile and consequently can live longer and grow larger than diploid congeners in many semelparous species (spawning only once) because they never reach maturity and post-spawning mortality is averted. Triploid fishes are also of interest to the commercial sector (larger fish are more valuable) and to fisheries management since sterile fish can potentially minimize negative impacts of escaped fish in the wild. RESULTS: The vast majority of genes in liver tissue had similar expression levels between diploid and triploid coho salmon, indicating that the same amount of mRNA transcripts were being produced per gene copy (positive gene dosage effects) within a larger volume cell. Several genes related to nutrition and compensatory growth were differentially expressed between diploid and triploid salmon, indicating that some loci are sensitive to cell size and/or DNA content per cell. To examine how robust expression between ploidies is under different conditions, a genetic/metabolic modifier in the form of different doses of a growth hormone transgene was used to assess gene expression under conditions that the genome has not naturally experienced or adapted to. While many (up to 1400) genes were differentially expressed between non-transgenic and transgenic fish, relatively few genes were differentially expressed between diploids and triploids with similar doses of the transgene. These observations indicate that the small effect of ploidy on gene expression is robust to large changes in physiological state. CONCLUSIONS: These findings are of interest from a gene regulatory perspective, but also valuable for understanding phenotypic effects in triploids, transgenics, and triploid transgenics that could affect their utility in culture conditions and their fitness and potential consequences of release into nature. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5655-8) contains supplementary material, which is available to authorized users.